The Influence of Digital Marketing on Purchase Intention with Brand Image as an Intervening Variable - Puteri Kamila (Publikasi Indonesia, 2026)
In the digital era, the rapid growth of internet use and social media has encouraged companies to adopt digital marketing strategies to influence consumer behavior and strengthen their competitive position. Digital marketing is considered an effective tool not only for delivering product information but also for shaping a positive brand image that may lead to higher purchase intention. This study examines the influence of digital marketing on purchase intention, positioning brand image as a mediating mechanism within the relationship. Drawing on contemporary digital consumer behavior perspectives, the research investigates how interactive and content-driven marketing activities shape consumers’ cognitive evaluations and behavioral intentions. A purposive sampling method was employed, involving 137 respondents residing in Semarang City who actively engage with digital platforms. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with WarpPLS 8.0 to assess both direct and indirect effects. The findings demonstrate that digital marketing significantly and positively affects brand image and purchase intention. Brand image also exerts a significant positive influence on purchase intention and partially mediates the relationship between digital marketing and purchase intention. These results suggest that digital marketing not only directly stimulates consumer buying intention but also operates indirectly by strengthening favorable brand perceptions. In conclusion, the results are useful for evaluating the implementation of digital marketing and brand image in increasing product purchase intention.